Enhancing Islamic Religious Learning Outcomes in Elementary Schools: Evaluating the Impact of the Differentiated Learning Model - Muhammad Anshori (AL-ISHLAH: Jurnal Pendidikan, 2025)
Differentiated learning is a pedagogical strategy designed to address the diverse learning needs of students, improving their engagement and comprehension. This approach is particularly relevant in Islamic religious education, where varying student backgrounds and skills necessitate adaptable teaching methods. This study examines the effectiveness of the differentiated learning model in enhancing learning outcomes in elementary-level Islamic religious education. This research employs a quantitative quasi-experimental design with a nonequivalent control group framework, utilizing a pretest-posttest approach. The study includes two class groups: class VA (35 students) as the experimental group and class VB (34 students) as the control group. A saturated sampling method was used, ensuring all students in both classes were included. Data were analyzed using an independent sample t-test to assess statistical significance. The pretest mean score for class VA was 68.2, while class VB scored 56.06. After implementing differentiated learning, the post-test mean score for class VA increased to 87.6, whereas class VB scored 71.09. The independent sample t-test yielded a p-value of 0.000 (p 0.05), indicating a statistically significant difference in learning outcomes between the two groups. The results demonstrate that the differentiated learning model significantly enhances student performance in Islamic religious education at the elementary level. These findings suggest that adopting differentiated instruction can improve learning effectiveness, making it a valuable strategy for educators.